Building Corporate Image Through Integrated Marketing Communication and Service Quality on Islamic Bank in Bandung - Resanti Lestari; yuyun Ratna; Vina Anggilia (EKSISBANK (Ekonomi Syariah dan Bisnis Perbankan), 2019)
Purposes. Aim of this research is to examines the effect of integrated marketing communications and Service Quality to the company 's image in Islamic banks in Bandung.Design/methodology/approach.This study is conducted in Bandung city and using Quantitative research design.The purpose of this study is to understand the perception of respondents towards their experience about corporate image in Islamic banking. this study were obtained by distributing survey questionnaire to a sample of 50 Owner Bank Syariahiness Enterprise in Bandung. Study assigned with purposive sampling which is particuar individuals are chossen with the characteristic relevant to the study who are thought will be most informative. Data analysis has been used Path Analysis. Findings this research. Corporate Image model on Islamic Bank in Indonesia is formed by performance of marketing communications and Service Quality. The second conclusion is Based on empirical evidence that obtained a correlation coefficient of 0.801, This shows that there is a very strong relationship between Integrated Marketing Communication and Service Quality simultaneously on Company Image. Coefficient determination for this model gained 0.641, this shows that Integrated Marketing Communication and Service Quality have an effect of 64.1% on Company Image, while the remaining 35.9% is explained by other things. F test is 41,957, this shows that simultaneously there is a significant influence between Integrated Marketing Communication and Service Quality on Company Image. And partialy the Integrated Marketing Communication variables directly affect of 62,1%. While the direct influence of Service Quality on the Company's image is 28,6%. Conclussion There are two conclusions of this study, the first is Model of the company's image is affected by marketing communications and service quality. The second conclusion Integrated Marketing Communication and Service Quality have an effect both partially and simultaneously on corporate image.